Analisis Sanitasi Lingkungan dan Status Gizi terhadap Kejadian Infeksi Saluran Pernapasan Akut (ISPA) pada Balita Pasca Bencana Banjir di Wilayah Kerja Puskesmas Panteraja Kabupaten Pidie Jaya - Zakia Ulrahmah; Hafni Zahara; Martina Martina (Jurnal Kesehatan Amanah, 2026)
Acute Respiratory Infection (ARI) remains a major public health problem in Indonesia. Based on the 2025 National Health Reporting System survey, ARI ranked first among diseases with the highest number of cases, reaching more than 14.5 million cases. This study aimed to determine and analyze the relationship between environmental sanitation and nutritional status with the incidence of ARI among children under five following flood disasters in the working area of Panteraja Community Health Center, Pidie Jaya Regency. The study employed a quantitative method with an analytical observational design using a case-control approach. The dependent variable was the incidence of ARI among under-five children, while the independent variables were environmental sanitation and nutritional status. The sample consisted of 122 children under five, including 61 children with ARI and 61 children without ARI. The results of the chi-square test showed a significant relationship between environmental sanitation and ARI incidence (p = 0.000; OR = 0.042; 95% CI = 0.014–0.133), as well as between nutritional status and ARI incidence (p = 0.000; OR = 0.011; 95% CI = 0.001–0.083). These findings indicate that poor environmental sanitation and inadequate nutritional status contribute to the occurrence of ARI among children under five after flooding. Therefore, promotive and preventive efforts, along with regular monitoring of children's nutritional status, are essential to reduce the risk of ARI.